Current advancements in CO2 capture using graphene-based materials - Gunarathna, Madushan Dhammika; Abeysinghe, Nimeshi Aviddika; Wickramaarachchi, Ashan Sithija; Kumari, Polegodage Dilushi Sureka Ruwan (European Journal of Chemistry, 2024)
In 2023, global CO2 emissions were 37.4 billion tonnes and a 1.1% increase compared to 2022. Although most countries try to decarbonize their economies, oil and gas supplied 52% of the world’s energy needs in 2021, and by 2050 it will be 47%. Therefore, in the future, oil and gas will still account for a considerable percentage of the energy sector. However, the continuous release of CO2 into the atmosphere at this rate can result in severe environmental problems. One of the promising approaches to address this issue is CO2 capture. This captured CO2 can then be stored underground or used to produce commercially valuable products. In recent years, graphene-based materials have gained attention in CO2 capture due to their interesting properties, such as high thermal stability and durability. This review focuses mainly on recently published articles on carbon capture using graphene-based materials.